Response of Periwinkle (Catharanthus roseus) to urea applications - suliman, ashwag; Jepreel, Howida T.; Idris, Tagelsir I. M.; A. Warrag, Mohamed Osman; Hussien, Fakhereldin Awad. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
This study aimed to investigate the response of Catharanthus roseus to various rates of urea applications under nursery conditions at Shambat, Khartoum North, Sudan. Five levels of urea (0, 2.5, 5, 7.5 and 10 g/plant) were tested as soil dressings in 25X30 cm plastic pots. The study was arranged in complete randomized design where each treatment was replicated seven times. Data were collected 4 months after applications. The high urea doses enhanced vegetative growth parameters, while flowering and fruiting of the plant were boosted by the lower urea doses. These results elucidated the beneficial response of Periwinkle to nitrogenous fertilizers and might be accompanied in efforts towards economical large scale production of the plant under the field conditions.